Penyuluhan Terhadap Petani Swadaya Kelapa Sawit Guna Peningkatan Ekonomi Masyarakat Desa Anaiwoi Kecamatan Tanggetada Kabupaten Kolaka - Helviani Helviani; Aan Wilhan Juliatmaja (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Oil palm is an important industrial plant producing cooking oil, industrial oil and fuel. Anaiwoi Village, Tanggetada District, Kolaka Regency is one of the locations of oil palm plantation centers in the province of Southeast Sulawesi. Palm oil is one of the major staples planted by the community in Anaiwoi village, Tanggetada district, Kolaka regency, almost all the people in this area depend on oil palm for their livelihood. A common problem faced by smallholder oil palm farmers in this region is the lack of information on proper oil palm cultivation and management. So far, independent smallholders or independent smallholders only know how to cultivate in general and have not thought about the many aspects that affect the growth of oil palm seedlings. The solution that can be provided comes in the form of advice related to good oil palm cultivation in accordance with agronomic principles so that the incomes of independent smallholders/independent oil palm grow. To get oil palm plants that can produce optimally, good oil palm cultivation is the main thing to understand. Plants grown according to the right agronomic principles will be able to grow and develop correctly to produce optimally.